2011
DOI: 10.2320/matertrans.m2011124
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Strength, Ductility and Corrosion Resistance in Ti-Mo Base Alloys by Controlling Mo Equivalency and Bond Order

Abstract: The crevice corrosion resistance in high chloride and high acidic solution at high temperature in Ti-15Mo-5Zr and Ti-15Mo-5Zr-1Fe alloys and the tensile properties at ambient temperature in Ti-15Mo-5Zr-1Fe alloy were investigated in this study. The crevice corrosion resistance in Ti-15Mo-5Zr alloy with a Mo equivalency of 18.2 mass%, which was previously reported to show a combination of the high yield strength and the significant uniform elongation, was almost twice as high as that in Ti-15Mo alloy when the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Although the Mo equivalency is an arbitrary parameter, Ti alloys can be arranged in a sequence in accordance with the stability of the ¢-phase by using the Mo equivalency, which is very useful and convenient for researchers developing new Ti-based alloys. 49,52) Thus, the critical concentration is of significant scientific and engineering value as a basis for determining Mo equivalency.…”
Section: Metastable Equilibrium Temperaturementioning
confidence: 99%
“…Although the Mo equivalency is an arbitrary parameter, Ti alloys can be arranged in a sequence in accordance with the stability of the ¢-phase by using the Mo equivalency, which is very useful and convenient for researchers developing new Ti-based alloys. 49,52) Thus, the critical concentration is of significant scientific and engineering value as a basis for determining Mo equivalency.…”
Section: Metastable Equilibrium Temperaturementioning
confidence: 99%
“…The addition of a sufficient amount of Molybdenum gives Titanium a very good resistance to corrosion [ 31 , 34 ]. In several studies [ 2 , 16 , 35 , 36 ], it is observed that a minimum percentage of 15 wt% Mo can lead to an increase in corrosion resistance in biological environments at high temperatures for titanium alloys [ 8 , 31 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…But the use of this material does not solve several problems [3][4][5][6][7] Starting with the results obtained by several researchers [8] a theoretical method for alloy design has been developed without any trial-and-error experiments. The design strategy has been developed by combined some parameters as: the bond order (Bo); the metal -orbital energy level (Md); the electron/atom (e/a) ratio, and the Mo equivalency [9,10].…”
mentioning
confidence: 99%